PERBAIKAN TANAH LUNAK DENGAN PENAMBAHAN TANAH BIASA PADA TIMBUNAN PADA TANAH RAWA (LUNAK) DI PROYEK PLTMG KASTELA - Jamalun Togubu; Irnawaty (JURNAL SIPIL SAINS, 2026)
Seaports are one of the most important transportation infrastructures that play a strategic role in regional and national economic growth. However, port activities have the potential to cause negative environmental impacts, such as marine water pollution, degradation of coastal habitats, and deterioration of air quality. This study aims to analyze environmentally based development strategies for Pelindo IV Ahmad Yani Port in Ternate using a sustainable development approach. The research employs a descriptive qualitative method, supported by field observations and policy document analysis. The results indicate the need for integration between port infrastructure planning and environmental management through the implementation of environmentally friendly principles, resource efficiency, and environmental impact monitoring and mitigation systems. This study recommends strengthening policies, adopting clean technologies, and enhancing stakeholder participation to achieve a productive and environmentally sustainable port. keywords: soils, soft, structure, ground